(untitled) (Ecological Perspective, 2025)
Overseeding is a practice that involves introducing new grass seeds into existing turf areas to enhance density, fill bare spots, and improve overall turf quality. This method plays a crucial role in maintaining the aesthetics and functionality of high-traffic areas such as sports fields, parks, and urban landscapes. In addition to improving the visual quality of turf, overseeding supports species diversity, contributing to increased resistance against pests and diseases. By selecting appropriate seeds and applying proper techniques, overseeding helps turf areas adapt to environmental conditions and achieve long-term durability. This method significantly influences turf density, color, resilience, and regeneration capacity, making it an integral part of sustainable turf management strategies. This study examines the application processes of overseeding, its impact on turf quality, and its importance in turf management practices.